EVOLUTIONARY AND ECOLOGICAL ASPECTS OF PLANT STRESS TOLERANCE - Abdulmalik G. Yusufov (Юг России: экология, развитие, 2018)
Abstract. Aim. The aim is to study the threshold sensitivity to salinization of the environment of individual isolated structures for evaluating the salt tolerance of plants. Methods. Comparison of the reaction to salinization of seeds, sprouts, epicotyls, leaves, cotyledons and flowers in species of cultural and natural flora. The following parameters were taken into account in the work: the life span, the time and capacity of for mation of roots and buds, and the wet and dry biomass of species. The results were processed by Statara version 3.0 Shareware (Statistic 5.0) by the parameters of the interaction of roots and shoots. Results. Plant individuals are characterized by the presence of structures that differ in specialization and life span. The question of the correspondence of reactions of structures with the salt tolerance of plants needs to be studied. The stability of the individual as an integral system is determined by the interaction of organs and structures with each other and with other components of the complex community. It evolves in the course of evolution by selecting individuals in the formation of stable plant communities. Quantitative methods of autoecology and genetics of populations are used to understand its mechanisms and role. Conclusion. The structure of an individual plant in an isolated culture is characterized by the specific reaction to salinization of the environment. In this case, the reaction of seeds, sprouts and isolated epicotyls corresponds most closely to the stability of the individual under the stress.